Strategi Peningkatan Pelayanan Persampahan Berbasis 3R di Kelurahan Jatihandap Melalui Penerapan Contingent Valuation Method - Muhammad Dimas Zulri; Iwan Juwana (Jurnal Serambi Engineering, 2020)
The increasing population in Indonesia is directly proportional to the growth of new settlements. In line with this, the growth of waste volume in Indonesia is closely related to the growth of its population. The level of welfare and lifestyle in Indonesia has resulted in a significant increase in waste generation, especially in urban areas. Jatihandap is one of the areas in Mandalajati Subdistrict, Bandung City that increases the influence of waste generation by each people and wants to improve the quality of its waste services to reduce these impacts. One way that can be done to measure the willingness of citizens to improve waste services is to measure the Contingent Valuation Method. Contingent Valuation Method (CVM) Based on the results of this study, WTP values were 138 people from 153 samples selected. The estimated WTP (EWTP) is Rp. 12,971 and the total WTP (TWTP) is Rp. 80,385,000 / month. Based on multiple linear regression analysis, the WTP value of Jatihandap Urban Village is influenced by the amount of garbage contributions and gender equality from the results of the questionnaire that has been done.